UNDERSTANDING TEACHING THROUGH EXPERIENCE: A STUDENT’S REFLECTIVE APPROACH TO BECOMING A CHRISTIAN TEACHER IN PSAL (PLANNING, STRATEGY, ASSESSMENT AND LEARNING) [MEMAHAMI MENGAJAR MELALUI PENGALAMAN: PENDEKATAN REFLEKTIF MAHASISWA DALAM MENJADI GURU KRISTEN MELALUI MATA KULIAH PSAP (PERENCANAAN, STRATEGI, ASESMEN, DAN PEMBELAJARAN)] - Yanti (Universitas Pelita Harapan, 2026)
This research explores the transformative process of student teachers as they transition into educators through reflective practices. Focusing on the personal experiences and reflections of student teachers, the study aims to understand how their experiences shape their development of calling, teaching competencies and pedagogy through the course PSAL (Planning, Strategy, Assessment and Learning). Using qualitative methods, the research highlights the role of self-reflection in enhancing how to make teaching plans, deciding on teaching strategies, assessment and conducting micro teaching in the classroom. By analyzing reflections report, the study investigates how student teachers reconcile theory with practice, identify areas of growth, and ultimately construct their professional identity as Christian educators. This reflective approach not only contributes to their understanding of teaching but also fosters a deeper connection to their future students and teaching practices. The findings underscore the importance of reflective practice as a foundational tool for developing Christian educators. Abstrak Bahasa Indonesia Penelitian ini mengeksplorasi proses transformatif calon guru saat mereka menjalani proses transisi menjadi pendidik melalui praktik reflektif. Dengan berfokus pada pengalaman pribadi dan refleksi calon guru, penulisan ini bertujuan untuk memahami bagaimana pengalaman mereka membentuk perkembangan panggilan, kompetensi mengajar, dan pedagogi mereka melalui mata kuliah PSAP (Perencanaan, Strategi, Asesmen, dan Pembelajaran). Dengan menggunakan metode kualitatif, penelitian ini berusaha menyoroti peran refleksi diri dalam meningkatkan kemampuan merancang rencana pelaksanaan pembelajaran, menentukan strategi mengajar, penilaian, dan melaksanakan micro teaching di kelas. Dengan menganalisis laporan refleksi, penelitian ini menyelidiki bagaimana calon guru menyatukan teori dengan praktik, mengidentifikasi area pengembangan, dan pada akhirnya membangun identitas profesional mereka sebagai pendidik Kristen. Pendekatan reflektif ini tidak hanya berkontribusi pada pemahaman mereka tentang pengajaran tetapi juga memperkuat koneksi yang lebih dalam dengan siswa mereka di masa depan dan praktik pengajaran mereka. Temuan ini menyoroti pentingnya praktik reflektif sebagai alat dasar untuk mengembangkan calon-calon pendidik Kristen.